2023
DOI: 10.3390/f14061124
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Simulated Nitrogen Deposition Has Moderate Impacts on Soil Microbial Communities across Three Bioclimatic Domains of the Eastern Canadian Forest

Abstract: The soil microbiome plays major roles in the below-ground processes and productivity of forest ecosystems. Atmospheric nitrogen (N) deposition is predicted to increase globally and might create disturbances in soil microbial communities, essentially by modifying soil chemistry. However, the impacts of higher N deposition on the soil microbiome in N-limited northern forests are still unclear. For 16 years, we simulated N deposition by adding ammonium nitrate at rates of 3 and 10 times the ambient N deposition d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 85 publications
3
0
0
Order By: Relevance
“…Like N, mechanisms of supplied P rapid uptake by microbes and plants could have occurred, especially because boreal forests are thought to be largely P limited (Maynard et al, 2014). All these observations echo findings from Renaudin et al (2023), who revealed that 16 years of N addition on the same experimental forest sites had very moderate impacts on the composition of soil bacterial and fungal communities while having no impact on soil microbial diversity. These conclusions, combined with the results of this study, support the idea that eastern Canadian boreal soils are generally resilient to N deposition.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Like N, mechanisms of supplied P rapid uptake by microbes and plants could have occurred, especially because boreal forests are thought to be largely P limited (Maynard et al, 2014). All these observations echo findings from Renaudin et al (2023), who revealed that 16 years of N addition on the same experimental forest sites had very moderate impacts on the composition of soil bacterial and fungal communities while having no impact on soil microbial diversity. These conclusions, combined with the results of this study, support the idea that eastern Canadian boreal soils are generally resilient to N deposition.…”
Section: Discussionsupporting
confidence: 89%
“…Our work also shows that foliar P and N:P were only affected by HN treatment, suggesting that atmospheric N deposition could create foliar N:P imbalance or P limitation only if current N deposition drastically undergoes a 10‐fold increase in the eastern Canadian boreal forest, which is unlikely in the near future. These findings, combined with previous results regarding the soil microbiome at the same experimental sites (Renaudin et al, 2023), suggest that soils of the eastern Canadian boreal forest were and will be resilient to higher N deposition. This should be considered to help guide future development and strategies for high‐latitude forestry, a particularly economically important activity in eastern Canada.…”
Section: Discussionsupporting
confidence: 81%
“…This outcome supports our initial hypothesis but contradicts previous findings that demonstrated the incorporation of N accelerating the litter decomposition rate in Camptotheca acuminata in the western areas of the Sichuan Basin [38]. Friedman's long-term experiments in the boreal hardwood forest ecosystem of Michigan aimed to increase atmospheric nitrogen deposition and decrease woodland decay [39]. These inconsistencies in the results can be partially attributed to variations in the level of experimental N addition [40].…”
Section: Simulation Of the Effect Of Nitrogen Deposition On Litter De...supporting
confidence: 51%